1997
DOI: 10.1002/(sici)1097-4636(199711)37:2<282::aid-jbm19>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A photochemical method for the surface modification of poly(etherurethanes) with phosphorylcholine-containing compounds to improve hemocompatibility

Abstract: Phosphorylcholine groups attached to polymer surfaces are known to improve hemocompatibility. A photochemical method is presented to couple phosphorylcholine-containing aryl azides to poly(etherurethane) surfaces (PEUs). Two aryl azides that consist of a photoactivatable 4-azidobenzoyl group, a short spacer chain, and a phosphorylcholine endgroup were synthesized. The two compounds differ only in the type of spacer used: triethylene glycol for compound 1 and hexanediol for compound 2. These compounds were phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…They are prone to aggregation in high ionic strength solutions in which the van der Waals attraction outweighs the electrostatic and/or steric repulsion provided by surface-bound ligands (e.g., citrate). Phosphorylcholine, as a very polar and zwitterionic molecule, can bind a large amount of water [14,15] . Whitesides et al [16] have shown that the strong resistance of zwitterionic SAMs to protein adsorption on flat surfaces is due to their strong hydration capacity via electrostatic interactions.…”
Section: Resultsmentioning
confidence: 92%
“…They are prone to aggregation in high ionic strength solutions in which the van der Waals attraction outweighs the electrostatic and/or steric repulsion provided by surface-bound ligands (e.g., citrate). Phosphorylcholine, as a very polar and zwitterionic molecule, can bind a large amount of water [14,15] . Whitesides et al [16] have shown that the strong resistance of zwitterionic SAMs to protein adsorption on flat surfaces is due to their strong hydration capacity via electrostatic interactions.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, a copolymer SB-Az Fig. 1 , which was a sulfobetaine polymer bearing photoreactive moiety, phenyl azide, was synthesized by AIBN polymerization, similarly 36,37 .…”
Section: Synthesis Of Polymersmentioning
confidence: 99%
“…Heiden et al [58] synthesized aromatic-azido polymers with phosphorylcholine groups and then grafted to biomaterial surface by UV irradiation (300-400 nm). The modified surface had high hydrophilicity, and much long clotting time.…”
Section: Modification Of Biomaterials Surface With Phosphorylcholinementioning
confidence: 99%